2017
DOI: 10.1002/anie.201710017
|View full text |Cite
|
Sign up to set email alerts
|

Ultralong Phosphorescence from Organic Ionic Crystals under Ambient Conditions

Abstract: A new type of materials, organic salts in the crystal state, have ultralong organic phosphorescence (UOP) under ambient conditions. The change of cations (NH , Na , or K ) in these phosphors gives access to tunable UOP colors ranging from sky blue to yellow green, along with ultralong emission lifetimes of over 504 ms. Single-crystal analysis reveals that unique ionic bonding can promote an ordered arrangement of organic salts in crystal state, which then can facilitate molecular aggregation for UOP generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
122
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 195 publications
(125 citation statements)
references
References 56 publications
3
122
0
Order By: Relevance
“…The same behaviour was observedf or all other derivatives studied except the photophysical parameters, which are strictly dependent on the different p-extended groups that have ad irect influence on the electronic properties of the luminogens. This p-extension goes along with ad rastic bathochromic shift compared to compound (24)( l = 483 nm) showing emission in the yellow to orange regiono ft he spectrum [see compound (35), l = 595 nm] whereas the lifetimes remainm ainly constant in the range of hundreds of milliseconds.…”
Section: Crystallisation-induced Phosphorescencementioning
confidence: 82%
“…The same behaviour was observedf or all other derivatives studied except the photophysical parameters, which are strictly dependent on the different p-extended groups that have ad irect influence on the electronic properties of the luminogens. This p-extension goes along with ad rastic bathochromic shift compared to compound (24)( l = 483 nm) showing emission in the yellow to orange regiono ft he spectrum [see compound (35), l = 595 nm] whereas the lifetimes remainm ainly constant in the range of hundreds of milliseconds.…”
Section: Crystallisation-induced Phosphorescencementioning
confidence: 82%
“…In this work, we designed and incubated a pair of chiral organic ionic crystals, terephtalic ( R / S )‐phenylethyamine (TPA‐( R / S )‐PEA), as shown in Figure , which generated LPP. It was found that the luminescence generated from the intermolecular charge‐transfer (CT) excitons and the phosphorescence was induced through the twisted TPA molecules, whose conformation was fixed by crystallization . With induced twisted molecular structure of planar TPA, two bands of phosphorescence were observed in crystals.…”
Section: Figurementioning
confidence: 99%
“…To understand the generation of different triplet states, computational analyses were conducted using Gaussian 09. The TPAs were considered as luminophores . As shown in Figure S4, each TPA anion is surrounded by six α‐PEA cations.…”
Section: Figurementioning
confidence: 99%
“…Ultralong organic phosphorescence (UOP), an ovel long persistent luminescent phenomenon, has become especially attractive in recent years [1] because materials with such afeature show great potential in sensing,displays,bioimaging, and anti-counterfeiting. [2] To obtain UOP materials,t remendous efforts have been devoted:1)the introduction of heavy halogen atoms,a romatic carbonyl groups,o ro ther substituents to accelerate intersystem crossing (ISC) between singlet and triplet excited states,a nd 2) providing ar igid molecular environment to suppress the nonradiation transitions and favoring UOP emission. [3] Among the reported strategies, such as polymerization and host-guest doping methods,etc., [4] crystal engineering is indispensable for obtaining UOP, because molecular motions can be efficiently restricted in ar igid crystal environment.…”
mentioning
confidence: 99%